Modeling Radiation Belt Electron Dropouts During Moderate Geomagnetic Storms Using Radial Diffusion Coefficients Estimated With Global MHD Simulations. Issue 9 (8th September 2022) - Silva, G. B. D.; Alves, L. R.; Tu, W.; Padilha, A. L.; Souza, V. M.; Li, L.‐F.; Lyu, X.; Pádua, M. B.
Abstract: Main phase flux dropouts often promote depletion of the outer electron radiation belt. The quantification of the contributions of various loss mechanisms to MeV electron dropouts has not yet been elucidated in detailed case studies for moderate geomagnetic storms. This work focuses on quantifying radial diffusion to study relativistic electron flux losses observed by Van Allen Probes during two moderate storms in 2017. The events are identified as Case 1 (27 March), with losses deep in L, and Case 2 (21 November), with less deep losses. Event‐specific radial diffusion coefficients ( D LL ) were calculated from global magnetohydrodynamic (MHD) fields simulated by the SWMF/BATS‐R‐US. The MHD‐ D LL was used as an input to radial diffusion simulations of both events for relativistic electrons. For the outer boundary conditions defined at L * = 6, electron fluxes measured by GOES‐15 at geosynchronous orbit were converted to phase space densities (PSDs) and then calibrated against the Van Allen Probe A measurements. Using these calibrated PSD of GOES‐15 at the outer boundary and event‐specific MHD‐ D LL, the main phase dropout is well captured with radial diffusion simulation for Case 2, but not for the deep dropout in Case 1 down to L * < 4.5. Scaling MHD‐ D LL based on validations of the MHD waves against in situ wave observations improves the simulation results of Case 1, but still does not fully resolve its deep dropout. However, analyzing the uncertainty of simulated PSD imposed by the uncertainty in the scaled MHD‐ D LL, it was found that outward radial diffusion could still account for the losses at L * < 4.5. Key Points: Two moderate geomagnetic storms with similar solar wind conditions produced MeV electron dropouts of different flux levels in the outer belt Radial diffusion simulations performed for the case studies using event‐specific D LL capture the main phase dropouts above L * = 4.5 Stronger outward radial diffusion loss or additional mechanism is needed to explain losses down to L * < 4.5 in the strong dropout case